CALICUM, Mg AND Na RELEASE KINETICS FROM SALINE- SODIC SOIL MIXED WITH SOME AMENDMENTS - & Al-Alwani, Al-Hadethi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the effect of phosphogypsum and humic acids on the leaching and releasing of salts from saline- sodic soil. A laboratory experiment was conducted in polyethylene columns (60.0 cm and 7.1 cm). The columns were filled with 30 cm soil (EC=73.78 dSm-1). The experiment included two factors, phosphogypsum added at levels 0, 5, 10 and 15 mtons ha-1 with symbols PG0,PG1, PG2 and PG3 respectively, and humic acids were added at levels 0, 50, 100 and 150 kg ha-1 with symbols HA0, HA1, HA2 and HA3, mixing them with the top 5 cm of soil column. The electrical conductivity and the concentrations of water soluble cations (Ca, Mg, and Na) in leachate were determined and sodium adsorption ratio (SAR) was calculated. Results showed that accumulative salts (TDS), sodium released from soil columns increased with increasing the level of addition, whether of phosphogypsum or humic acids. The highest value of salts and sodium released was 682.63 g L-1 and 7086.12 mmol L-1 respectively in the treatment PG3HA3, while the lowest value was 455.94 g L-1 and 3899.40 mmol L-1 respectively in the treatment PG0HA0. Calcium (mmol L-1) increased by increasing the level of phosphogypsum, decreased by increasing the level of humic acids, the highest value of accumulated calcium was 1599.0 mmol L-1 in PG3HA0 while the lowest value was 820.53 mmol L-1 in PG0HA3. The results showed that the best equation for describing release kinetics of sodium adsorption ratio in soil is the diffusion equation. Increasing level of phosphogypsum and humic acids increased the release constant velocity (K) of sodium adsorption ratio.